A peptide mimetic targeting trans-homophilic NCAM binding sites promotes spatial learning and neural plasticity in the hippocampus. - Igor Kraev; Christian Henneberger; Clara Rossetti; Lisa Conboy; Lene B Kohler; Martina Fantin; Alistair Jennings; Cesar Venero; Victor Popov; Dmitri Rusakov; Michael G Stewart; Elisabeth Bock; et al. (PLoS ONE)
The key roles played by the neural cell adhesion molecule (NCAM) in plasticity and cognition underscore this membrane protein as a relevant target to develop cognitive-enhancing drugs. However, NCAM is a structurally and functionally complex molecule with multiple domains engaged in a variety of actions, which raise the question as to which NCAM fragment should be targeted. Synthetic NCAM mimetic peptides that mimic NCAM sequences relevant to specific interactions allow identification of the most promising targets within NCAM. Recently, a decapeptide ligand of NCAM--plannexin, which mimics a homophilic trans-binding site in Ig2 and binds to Ig3--was developed as a tool for studying NCAM's trans-interactions. In this study, we investigated plannexin's ability to affect neural plasticity and memory formation. We found that plannexin facilitates neurite outgrowth in primary hippocampal neuronal cultures and improves spatial learning in rats, both under basal conditions and under conditions involving a deficit in a key plasticity-promoting posttranslational modification of NCAM, its polysialylation. We also found that plannexin enhances excitatory synaptic transmission in hippocampal area CA1, where it also increases the number of mushroom spines and the synaptic expression of the AMPAR subunits GluA1 and GluA2. Altogether, these findings provide compelling evidence that plannexin is an important facilitator of synaptic functional, structural and molecular plasticity in the hippocampal CA1 region, highlighting the fragment in NCAM's Ig3 module where plannexin binds as a novel target for the development of cognition-enhancing drugs.